Ownership and the Changing Employment Relationship: Why Stylized Notions of Labor No Longer Generally Apply—A Reply to Zardkoohi and Paetzold - Rousseau, Denise M.; Shperling, Zipi (Academy of Management Review, 2004)
Denise M. Rousseau, Zipi Shperling, Ownership and the Changing Employment Relationship: Why Stylized Notions of Labor No Longer Generally Apply: A Reply to Zardkoohi and Paetzold, The Academy of Management Review, Vol. 29, No. 4 (Oct., 2004), pp. 562-569